2011
DOI: 10.1111/j.1549-8719.2011.00094.x
|View full text |Cite
|
Sign up to set email alerts
|

Combined Oral Contraceptive Pills Containing Desogestrel or Drospirenone Enhance Large Vessel and Microvasculature Vasodilation in Healthy Premenopausal Women

Abstract: COCs containing 150 μg DSG or 3 mg DR significantly increase endothelium-dependent vasodilation in both large vessels and peripheral microvasculature. These effects may be due to the progestins exhibiting differential effects on eNOS expression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 50 publications
0
19
2
Order By: Relevance
“…As there is evidence that smoking, and mixed evidence that contraceptives, have an effect on endothelial function, cholesterol and blood pressure, their influence on the results of the current study were examined (Celermajer et al, 1993;Franceschini et al, 2013;Heidarzadeh et al, 2014;Ozaki et al, 2010;Thompson et al, 2011;Toda and Toda, 2010;Virdis et al, 2003). The results remained unchanged when either smoking or contraceptive use were included as covariates.…”
Section: Cardiovascular Factorsmentioning
confidence: 83%
“…As there is evidence that smoking, and mixed evidence that contraceptives, have an effect on endothelial function, cholesterol and blood pressure, their influence on the results of the current study were examined (Celermajer et al, 1993;Franceschini et al, 2013;Heidarzadeh et al, 2014;Ozaki et al, 2010;Thompson et al, 2011;Toda and Toda, 2010;Virdis et al, 2003). The results remained unchanged when either smoking or contraceptive use were included as covariates.…”
Section: Cardiovascular Factorsmentioning
confidence: 83%
“…In contrast to the negative impact of hyperglycaemia, oestrogen has well‐established protective effects on endothelial function. For example, elevated synthetic oestrogen levels can improve FMD in postmenopausal women on oestrogen hormone replacement therapy (Hashimoto et al., ; Lieberman et al., ; Sherwood et al., ), and in premenopausal women on oral contraceptive pills (Meendering, Torgrimson, Miller, Kaplan, & Minson, ; Thompson, Przemska, Vasilopoulou, Newens, & Williams, ). Likewise, it has often been shown that FMD is augmented during the late follicular (LF) phase of the natural menstrual cycle, when oestrogen (estradiol) levels are elevated (Adkisson et al., ; Harris, Tedjasaputra, Zhao, & Richardson, ; Hashimoto et al., ; Kawano et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…FMD of the brachial artery was measured by trained researchers using an ATL Ultrasound HDI5000 broadband ultrasound system (ATL Ultrasound, Bothell, Washington) and a procedure based on standard guidelines, as previously described [16] . Briefly, following baseline imaging, a blood pressure cuff was inflated to 220 mm Hg to occlude blood flow for 5 min.…”
Section: Methodsmentioning
confidence: 99%